Solid electrolyte for all-solid-state secondary battery, composite electrode, all-solid-state secondary battery and method for preparing solid electrolyte
Through the solid electrolyte structure of Li7-xPS6-xBrx, combined with mechanical grinding and heat treatment technology, the problems of high activation energy and poor temperature stability of sulfur-silver germanium ore solid electrolyte are solved, and the high ionic conductivity and temperature of all-solid secondary batteries are achieved. stability.
Patent Information
- Application Number
- CN201811306143.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-10-26
- Filing Date
- 2018-11-05
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2038-11-05
AI Technical Summary
The existing solid electrolytes of sulfur silver germanium ore lead to poor temperature stability with high activation energy and insufficient ionic conductivity, making it difficult to maintain stability at various temperatures.
The solid electrolyte with a constituent structure of Li7-xPS6-xBrx was used to ensure that it had a sulfur-silver germanium ore crystal structure through CuKα radiation X-ray diffraction analysis, and the activation energy was reduced through mechanical grinding and heat treatment while maintaining high ionic conductivity.
It achieves a stable high ionic conductivity and low activation energy at various temperatures, and improves the temperature stability of all-solid-state secondary batteries.
Smart Images

Figure BDA0001853660040000231 
Figure BDA0001853660040000232 
Figure BDA0001853660040000241
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of and priority to Japanese Patent Application No. 2017-0219084 filed in the Japan Patent Office on November 14, 2017, and Korean Patent Application No. 2018-0129354 filed in the Korean Patent Office on October 26, 2018, and the contents of which are incorporated herein by reference in their entirety. Technical Field
[0003] The present disclosure relates to a solid electrolyte for an all-solid-state secondary battery, an all-solid-state secondary battery, and a method of preparing the solid electrolyte. Background Art
[0004] As an alternative to non-aqueous electrolytes for secondary batteries, all-solid-state secondary batteries including solid electrolytes have been tested for use as secondary batteries. Since all-solid-state secondary batteries are completely solid, they do not contain flammable organic solvents in the battery. Thus, all-solid-state secondary batteries using solid electrolytes are considered to have better safety properties than secondary batteries using non-aqueous electrolytes.
[0005] The solid electrolyte used in the all-solid-state secondary battery may have an ionic conductivity lower than that of the non-aqueous electrolyte. Therefore, research and development are underway to improve the ionic conductivity of the solid electrolyte. Recently, a solid electrolyte having an argyrodite crystal structure (hereinafter referred to as "argyrodite solid electrolyte") has been examined as promising because the argyrodite solid electrolyte has a relatively high ionic conductivity (e.g., about 10 -4 S / cm-10 -3 S / cm). Argentumite solid electrolytes are known, for example, in Japanese Patent No. 2016-24874, International Patent Publication No. WO 2016 / 009768, Japanese Patent No. 5957144, International Patent Publication No. WO 2015 / 011937, International Patent Publication No. WO2015 / 012042, Japanese Patent No. 2011-96630, and Japanese Patent No. 2015-72783. Solid electrolytes having an argyrodite crystal structure have been found to have undesirably high activation energies, for example, 30 kilojoules / mole (kJ / mol) or greater. Having a high activation energy results in poor temperature stability, and thus the properties of the argyrodite solid electrolyte may vary significantly depending on the temperature of use.
[0006] Therefore, there is a need for improved solid electrolytes that are stable to lithium, have suitable ionic conductivity and activation energy, and are stable over a wide range of usage temperatures. Summary of the invention
[0007] In this regard, the present disclosure provides a all-solid-state secondary battery using a solid electrolyte for an all-solid-state secondary battery and a method for preparing the solid electrolyte, wherein the solid electrolyte can reduce the activation energy while maintaining the high ionic conductivity of the solid electrolyte having an argyrodite crystal structure.
[0008] Additional aspects will be set forth in part in the following description, and in part will be obvious from the description, or may be learned by practice of the presented embodiments.
[0009] According to an aspect of an embodiment, there is provided a solid electrolyte for an all-solid-state secondary battery, the solid electrolyte having a composition represented by the formula (1):
[0010] Li 7-x PS 6-x Br x ...(1),
[0011] where 1.2 < x < 1.75, the solid electrolyte has an argyrodite crystal structure, and when analyzed by X-ray diffraction using CuKα radiation, the solid electrolyte has at least one peak at a position of 29.65 ± 0.50° 2θ.
[0012] In an embodiment, x in formula (1) may satisfy the range of 1.23 ≤ x ≤ 1.5.
[0013] In an embodiment, the solid electrolyte may further satisfy (IB / IA) < 0.5, where when analyzed by X-ray diffraction using CuKα radiation, IA is the maximum intensity of the peak at the position of 29.65° ± 0.50° 2θ, and IB is the maximum intensity of the peak at the position of 28.00° ± 0.50° 2θ.
[0014] In an embodiment, IB / IA may be less than 0.1.
[0015] In an embodiment, the solid electrolyte can reduce the activation energy while maintaining its high ionic conductivity.
[0016] In an embodiment, when analyzed by X-ray diffraction, the solid electrolyte may have peaks at positions of 25.16° ± 0.50° 2θ, 29.65° ± 0.50° 2θ, 30.94° ± 0.50° 2θ, 44.36° ± 0.50° 2θ, 47.22° ± 0.50° 2θ, and 51.75° ± 0.50° 2θ.
[0017] In an embodiment, the solid electrolyte for an all-solid-state secondary battery may have an activation energy of about 29 kJ / mole or less.
[0018] In an embodiment, the solid electrolyte for the all-solid-state secondary battery may have an ionic conductivity of about 1.6 x 10 -3 Siemens per centimeter (S / cm) or higher at a temperature of 27 °C.
[0019] According to another aspect of an embodiment, a composite electrode is provided, which includes an electrode active material and a first solid electrolyte, and the first solid electrolyte is the above-mentioned solid electrolyte.
[0020] In an embodiment, the electrode active material may be a positive electrode active material or a negative electrode active material.
[0021] In an embodiment, the composite electrode may further include a second solid electrolyte different from the first solid electrolyte.
[0022] In an embodiment, the composite electrode may further include a sulfide solid electrolyte.
[0023] According to another aspect of an embodiment, an all-solid-state secondary battery is provided, which includes: a positive electrode layer; a negative electrode layer; and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer and including a first solid electrolyte, and the first solid electrolyte is the above-mentioned solid electrolyte.
[0024] In an embodiment, the positive electrode layer may include a positive electrode active material, and the positive electrode active material may include a lithium-containing ternary transition metal oxide having a layered rock salt structure.
[0025] In an embodiment, the lithium-containing ternary transition metal oxide may be represented by LiNi x Co y Al z O 2 or LiNi x Co y Mn z O 2 where x, y, and z may satisfy 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1.
[0026] In an embodiment, the negative electrode layer includes a negative electrode active material, and the negative electrode active material may include at least one of the following: lithium metal, a metal capable of alloying with lithium, or a carbonaceous material.
[0027] In an embodiment, the negative electrode active material includes: lithium (Li), indium (In), aluminum (Al), tin (Sn), silicon (Si), artificial graphite, graphite carbon fiber, resin sintered carbon, pyrolysis vapor grown carbon, coke, intermediate carbon microbeads (MCMB), furfuryl alcohol, polyphenylene (polyphenylene), pitch-based carbon fiber (carbon fiber based on furfuryl alcohol, polyphenylene (polyphenylene), pitch), vapor grown carbon fiber, natural graphite, non-graphitizable carbon, or a combination thereof.
[0028] In an embodiment, the solid electrolyte layer may further include a second solid electrolyte different from the first solid electrolyte.
[0029] In an embodiment, the solid electrolyte layer may further include a sulfide solid electrolyte.
[0030] In an embodiment, the solid electrolyte may improve the temperature stability of the all-solid-state secondary battery.
[0031] According to another embodiment, a method for preparing a solid electrolyte is provided, the method comprising: mixing Li 2 S.P. 2 S 5 , and LiBr to obtain a glassy composite; and heat treating the glassy composite at a temperature of the glass transition temperature of the glassy composite or greater to convert the glassy composite into an ion-conducting glass-ceramic and obtain a solid electrolyte, wherein the solid electrolyte has a composition represented by formula (1):
[0032] Li 7-x PS 6-x Br x ...(1),
[0033] Of which 1.2 <x<1.75。
[0034] In an embodiment, the mechanical milling may be performed at a temperature of about 25° C. and in an inert atmosphere.
[0035] In an embodiment, the mechanical grinding may be performed by a planetary ball mill.
[0036] In an embodiment, the mechanical milling using a planetary ball mill may be operated at a rotation speed of about 50 to about 600 rpm for 0.1 to 50 hours.
[0037] In an embodiment, the heat treatment is performed at a temperature in a range of about 250°C to about 450°C.
[0038] In an embodiment, the method may further include cooling the ion-conducting glass-ceramic after performing the heat treatment of the glassy composite to obtain a solid electrolyte.
[0039] In an embodiment, the solid electrolyte may have an argyrodite crystal structure.
[0040] In an embodiment, a solid electrolyte providing reduced activation energy while maintaining high ionic conductivity of an argyrodite-type solid electrolyte may be easily and reliably prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] These and / or other aspects will become apparent and more readily appreciated from the following description of the embodiments considered in conjunction with the accompanying drawings, in which:
[0042] Figure 1 is a graph of intensity (arbitrary units (au)) versus diffraction angle (degrees, 2 theta (2θ)) showing the results of X-ray diffraction measurements using CuKα radiation performed on solid electrolytes prepared according to Examples 1-7 of the present disclosure;
[0043] Figure 2 is a schematic diagram of an all-solid-state secondary battery according to an embodiment; and
[0044] Figure 3 : is a graph of intensity (au) versus diffraction angle (2θ), which shows the results of X-ray diffraction measurement using CuKα radiation performed on the solid electrolytes prepared according to Comparative Examples 1 to 16 of the present disclosure. DETAILED DESCRIPTION
[0045] Embodiments will now be described in detail, examples of which are shown in the accompanying drawings, wherein the same reference numerals refer to the same elements throughout. In this regard, the present embodiment may have different forms and should not be construed as being limited to the description set forth herein. Therefore, the following embodiments are described only by reference to the accompanying drawings to illustrate aspects. Expressions such as "at least one (kind)" modify the entire list of elements when before or after a list of elements without modifying the individual elements of the list.
[0046] If not otherwise defined, all terms (including technical and scientific terms) in the specification may be defined as commonly understood by those skilled in the art. Terms defined in commonly used dictionaries may not be idealized or over-interpreted unless clearly defined. In addition, unless explicitly described to the contrary, the term "includes (comprising)" will be understood to mean including the elements described, but not excluding any other elements.
[0047] The terms used herein are only for the purpose of describing specific embodiments and are not intended to be limiting. As used herein, the singular forms "a, an" and "said" are intended to include plural forms, including "at least one", unless the content clearly indicates otherwise. "At least one" is not to be interpreted as limiting "a". It will be further understood that the terms "include" or "comprise" when used in this specification indicate the presence of the described features, regions, wholes, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more additional features, regions, wholes, steps, operations, elements, components and / or their collections.
[0048] In the drawings, the thickness of layers, films, panels, regions, etc., are exaggerated for clarity. Like reference numerals refer to like elements throughout the specification.
[0049] It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element or intervening layers may also be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements.
[0050] It will be understood that although the terms "first", "second", "third", etc. may be used herein to describe various elements, components, regions, layers and / or parts (segments), these elements, components, regions, layers and / or parts (segments) should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or part (segment) from another element, component, region, layer or part (segment). Therefore, without departing from the teachings herein, the "first element", "component", "region", "layer" or "part (segment)" discussed below may be referred to as a second element, component, region, layer or part (segment).
[0051] In addition, relative terms such as "lower" or "bottom" and "upper" or "top" may be used herein to describe the relationship of one element to another element as shown in the accompanying drawings. It will be understood that the relative terms are intended to include different orientations of the device in addition to the orientation depicted in the accompanying drawings. For example, if the device in one of the accompanying drawings is turned over, the element described as being on the "lower" side of the other element will then be positioned on the "upper" side of the other element. Therefore, the exemplary term "lower" may include both the "lower" and "upper" orientations, depending on the specific orientation of the accompanying drawings. Similarly, if the device in one of the accompanying drawings is turned over, the element described as being "below" or "beneath" the other element will then be oriented as "above" the other element. Therefore, the exemplary terms "below..." or "below..." may include both the orientations above and below.
[0052] As used herein, "about" or "approximately" includes the stated value and means within an acceptable deviation range for a particular value as determined by one of ordinary skill in the art in view of the measurements discussed and the errors associated with the measurement of a particular quantity (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations of the stated value, or within ±30%, 20%, 10%, or 5%.
[0053] Hereinafter, embodiments will be described in further detail by referring to the accompanying drawings. In addition, the same reference numerals in this specification and the drawings denote the same elements, and thus their descriptions may be omitted to limit repetition. The description of the embodiments is provided herein as examples and is not intended to show their equivalents or uses.
[0054] Configuration of the solid electrolyte
[0055] First, the configuration of the solid electrolyte according to the embodiment will be described. The solid electrolyte according to the embodiment may have a composition represented by formula (1):
[0056] Formula (1)
[0057] Li 7-x PS 6-x Br x
[0058] where 1.2 < x < 1.75.
[0059] Any suitable sub-range can be selected from the range of 1.2 < x < 1.75. For example, x may have a lower limit of 1.23 or greater, 1.25 or greater, or 1.5 or greater, but the embodiments of the present disclosure are not limited thereto. In an embodiment, 1.23 < x < 1.75, 1.25 < x < 1.75, or 1.5 < x < 1.75. When x satisfies the above conditions, the ionic conductivity of the solid electrolyte can be increased, and at the same time, the activation energy of the solid electrolyte can be reduced.
[0060] In the solid electrolyte having the composition represented by formula (1), the sulfur (S) atom in the compound Li 7 PS 6 is replaced by a bromine (Br) atom to provide Li 7 PS 6 having a crystal structure substantially the same as that of Li 7-x PS 6-x Br x. The solid electrolyte may have a argyrodite crystal structure. X-ray diffraction using CuKα radiation may be performed to determine whether the solid electrolyte has a argyrodite crystal structure. The argyrodite crystal structure is a tetrahedral close-packed cubic unit cell (unit cell) having an F4-3m space group. Structural features include an interpenetrating centered icosahedral anion framework that provides ideal and distorted tetrahedral cation sites. For a solid electrolyte having a composition represented by formula (1), lithium atoms and phosphorus atoms fill tetrahedral interstices (gaps) to form isolated PS within a close-packed structure. 4 3- Tetrahedron and LiS 4 3- A network of tetrahedrons.
[0061] In an embodiment, when the solid electrolyte is analyzed by X-ray diffraction using CuKα radiation, at least one peak may appear at a position of 29.65±0.50°2θ in the X-ray diffraction spectrum. In an embodiment, when analyzed by X-ray diffraction, peaks may appear at positions of 25.16°±0.50°2θ, 29.65°±0.50°2θ, 30.94°±0.50°2θ, 44.36°±0.50°2θ, 47.22°±0.50°2θ, and 51.75°±0.50°2θ. When the solid electrolyte has peaks at these positions when analyzed by X-ray diffraction, the solid electrolyte may have an Argentumite crystal structure.
[0062] Then, when the maximum intensity of the peak at the position of 29.65°±0.50°2θ is referred to as IA, and the maximum intensity of the peak at the position of 28.00°±0.50°2θ is referred to as IB, the peak intensity ratio IB / IA may be less than 0.5. In an embodiment, IB / IA may be less than 0.1, and at this point, the characteristics of the solid electrolyte may be further improved. Here, the peak at IA may be a peak corresponding to the argyrodite crystal structure as described above. The peak at IB may correspond to an impurity peak. Therefore, when IB / IA decreases, the characteristics of the solid electrolyte (in detail, ionic conductivity, etc.) may be improved. In an embodiment, IB may be 0. Figure 1 (which is described in detail below) shows the results of X-ray diffraction analysis of the solid electrolyte.
[0063] Thus, the solid electrolyte according to the embodiment may have an argyrodite crystal structure, and may be a composition represented by Formula (1). Therefore, the solid electrolyte according to the embodiment may have low activation energy while having excellent ion conductivity.
[0064] The solid electrolyte according to the embodiment may have a relative humidity of about 1.6 x 10 -3Siemens / cm (S / cm) - about 5.5 x 10 -3 S / cm, for example, about 1.7 x 10 -3 S / cm-approx. 5.5 x 10 -3 S / cm, about 1.8x 10 -3 S / cm-approx. 5.5 x 10 -3 S / cm, about 1.9x 10 -3 S / cm-approx. 5.5 x 10 -3 S / cm, about 2.0x 10 -3 S / cm-approx. 5.5 x 10 -3 S / cm, about 2.1x 10 -3 S / cm-approx. 5.5 x 10 -3 S / cm, about 2.2x 10 -3 S / cm-approx. 5.5 x 10 -3 S / cm, about 2.3x 10 -3 S / cm-approx. 5.5 x 10 -3 S / cm, about 2.4x10 -3 S / cm-approx. 5.5 x 10 -3 S / cm, about 2.5x 10 -3 S / cm-approx. 5.5 x 10 -3 S / cm, about 2.6x 10 -3 S / cm-approx. 5.5 x 10 -3 S / cm, about 2.7x 10 -3 S / cm-approx. 5.5 x 10 -3 S / cm, about 2.8x 10 -3 S / cm-approx. 5.5 x 10 -3 S / cm, or about 2.9 x 10 -3 S / cm-approx. 5.5 x 10 -3 The ionic conductivity is in the range of S / cm.
[0065] The applicant surprisingly found that when, as in formula (1), the compound Li 7 PS 6 When sulfur (S) atoms in the electrolyte are replaced by bromine (Br) atoms, the resulting solid electrolyte may have an activation energy that is reduced from about 35 kilojoules / mole (kJ / mol) to less than about 30 kJ / mol. Without wishing to be bound by theory, it is believed that the activation energy is reduced because the replacement by bromine atoms reduces conductivity (electronic conductivity) without significantly affecting ionic conductivity.
[0066] The solid electrolyte according to the embodiment may have an activation energy of less than about 30 kJ / mol, for example, about 29 kJ / mol or less, about 28.9 kJ / mol or less, about 28.8 kJ / mol, about 28.7 kJ / mol or less, about 28.6 kJ / mol or less, about 28.5 kJ / mol or less, about 28.4 kJ / mol or less, about 28.3 kJ / mol or less, about 28.2 kJ / mol or less, about 28.1 kJ / mol or less, about 28.0 kJ / mol or less, about 27.5 kJ / mol or less, about 27.0 kJ / mol or less, about 26.5 kJ / mol or less, about 26.0 kJ / mol or less, or about 25.5 kJ / mol or less.
[0067] Configuration of all-solid-state secondary battery
[0068] Next, by referring to Figure 2 , the configuration of the all-solid-state secondary battery 1 according to the embodiment will be described. Configuration of the positive electrode layer 10
[0069] The positive electrode layer 10 may have a positive electrode current collector 11 and a positive electrode active material layer 12. The positive electrode current collector 11 may be a plate (platelet) type or a film type, and each may include indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. In an embodiment, the use of the positive electrode current collector 11 may be omitted.
[0070] The positive electrode active material layer 12 may include a positive electrode active material and a solid electrolyte to constitute a composite positive electrode. In an embodiment, the solid electrolyte included in the positive electrode active material layer 12 may be a solid electrolyte having a composition represented by formula (1) according to an embodiment (also referred to herein as "solid electrolyte of formula (1)" for convenience). Alternatively, the solid electrolyte included in the positive electrode active material layer 12 may be a mixture of a solid electrolyte of formula (1) and a solid electrolyte different from the solid electrolyte of formula (1) according to an embodiment. An example of a solid electrolyte different from the solid electrolyte of formula (1) according to an embodiment will be described below. In addition, the solid electrolyte of formula (1) according to an embodiment may be included in one or more of the positive electrode layer 10, the negative electrode layer 20, and the solid electrolyte layer 30, wherein one or more of the solid electrolytes or mixtures of solid electrolytes in each of these layers may include a solid electrolyte of formula (1) according to an embodiment.
[0071] The positive electrode active material may be a material capable of reversibly intercalating and deintercalating lithium ions.
[0072] For example, the positive electrode active material may be at least one composite oxide of lithium and a metal selected from Co, Mn, Ni, and a combination thereof. For example, the positive electrode active material may be a compound represented by one of the following formulae: Li a A 1-b B 1 b D 1 2 (where 0.90≤a≤1.8 and 0≤b≤0.5); Li a E 1-b B 1 b O 2-c D 1 c (where 0.90≤a≤1.8, 0≤b≤0.5, and 0≤c≤0.05); LiE 2-b B 1 b O 4-c D 1 c (where 0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Co b B 1 c D 1 α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α≤2); Li a Ni 1-b-c Co b B 1 c O 2-α F 1 α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Co b B 1 c O 2-α F 1 2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Mn b B 1 c D 1 α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2); Lia Ni 1-b- c Mn b B 1 c O 2-α F 1 α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Mn b B 1 c O 2-α F 1 2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni b E c G d O 2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, and 0.001≤d≤0.1); Li a Ni b Co c Mn d G e O 2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, and 0.001≤e≤0.1); Li a NeG b O 2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a CoG b O 2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1.); Li a MnG b O 2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a Mn 2 G b O 4 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); QO 2 ;QS 2 ;LiQS 2 ; V 2 O 5 ;LiV 2 O 5 ;LiI 1 O2 ;LiNiVO 4 ;Li (3-f) J 2 (PO 4 ) 3 (where 0≤f≤2); Li (3-f) Fe 2 (PO 4 ) 3 (where 0≤f≤2); and LiFePO 4 .
[0073] In the above formula, A can be nickel (Ni), cobalt (Co), manganese (Mn), or a combination thereof; B 1 It may be aluminum (Al), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), iron (Fe), magnesium (Mg), strontium (Sr), vanadium (V), a rare earth element, or a combination thereof; D 1 It can be oxygen (O), fluorine (F), sulfur (S), phosphorus (P), or a combination thereof; E can be cobalt (Co), manganese (Mn), or a combination thereof; F 1 It can be fluorine (F), sulfur (S), phosphorus (P), or a combination thereof; G can be aluminum (Al), chromium (Cr), manganese (Mn), iron (Fe), magnesium (Mg), lanthanum (La), cerium (Ce), strontium (Sr), vanadium (V), or a combination thereof; Q can be titanium (Ti), molybdenum (Mo), manganese (Mn), or a combination thereof; I 1 It can be chromium (Cr), vanadium (V), iron (Fe), scandium (Sc), yttrium (Y), or a combination thereof; and J can be vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), nickel (Ni), copper (Cu), or a combination thereof.
[0074] For example, the positive electrode active material may be formed from a lithium salt such as lithium cobalt oxide (LCO), lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum (NCA) oxide, lithium nickel cobalt manganese (NCM) oxide, lithium manganese oxide, lithium iron phosphate, nickel sulfide, copper sulfide, sulfur, iron oxide, vanadium oxide, or a combination thereof. The positive electrode active material may be used alone or as a combination of at least two selected therefrom.
[0075] In addition, the positive electrode active material can be formed by: a lithium salt of a transition metal oxide having a layered rock salt structure included in the above-mentioned lithium salt. Here, the term "layered" as used herein refers to a thin layer shape, and the term "rock salt structure" as used herein refers to a sodium chloride type structure as a crystal structure. In detail, the layered rock salt structure refers to a structure in which a face-centered cubic lattice formed by cations and anions, respectively, displaces (moves) half of the side of each unit lattice (unit cell).
[0076] Examples of the lithium salts of the transition metal oxides having a layered rock salt structure may include lithium salts of ternary transition metal oxides, such as LiNi x Co y Al z O 2 (NCA) or LiNi x Co y Mn z O 2 (NCM) (where 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1).
[0077] When the positive electrode active material includes a lithium salt of a ternary transition metal oxide having the above-described layered rock salt structure, the all-solid-state secondary battery 1 may have improved energy density and thermal stability.
[0078] The positive electrode active material may be covered with a coating layer. Here, any suitable coating layer can be used as the coating layer according to the embodiment, including the coating layers known for the positive electrode active materials of all-solid-state secondary batteries. Examples of the coating layer may be Li 2 O-ZrO 2 .
[0079] In an embodiment, the positive electrode active material may be composed of a lithium salt of a ternary transition metal oxide such as NCA or NCM. When Ni is included as the positive electrode active material, the capacity density of the all-solid-state secondary battery 1 can be increased, and at the same time, the elution of metal from the positive electrode active material in the charged state can be reduced. Therefore, the all-solid-state battery 1 according to the embodiment may have improved long-term reliability and cycle characteristics in the charged state and / or during charging.
[0080] Here, the positive electrode active material may have a shape such as a spherical particle shape or an elliptical particle shape. In addition, the average particle diameter D50 of the positive electrode active material is not particularly limited and may be within the range applicable to the positive electrode active materials for all-solid-state secondary batteries. In addition, the amount of the positive electrode active material used for the positive electrode layer 10 is not particularly limited and may be within the range applicable to the positive electrode active materials for the all-solid-state secondary battery 1.
[0081] In addition, in order to prepare the positive electrode layer 10, additives such as a conductive agent, a binder, a filler, a dispersant, or an ion conductive agent may be appropriately mixed in addition to the positive electrode active material and the solid electrolyte described above.
[0082] For example, graphite, graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or metal powder can be used as a conductive agent that can be used in the positive electrode layer 10. In addition, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, or polyethylene can be used as a binder that can be used in the positive electrode layer 10. Next, for the filler, dispersant, or ion conductive agent that can be used in the positive electrode layer 10, known materials commonly used in electrodes of all-solid-state secondary batteries can be used. Negative electrode layer
[0083] The negative electrode layer 20 may include a negative electrode current collector 21 and a negative electrode active material layer 22. The negative electrode current collector 21 may be, for example, a plate type or a film type, each of which is composed of In, Cu, Mg, stainless steel, Ti, Fe, Co, Ni, Zn, Al, Ge, Li, or an alloy thereof. The use of the negative electrode current collector 21 may be omitted.
[0084] The negative electrode active material layer 22 may include a negative electrode active material and a solid electrolyte to form a composite negative electrode. The negative electrode active material may have a charge / discharge voltage lower than the charge / discharge voltage of the positive electrode active material, and may be composed of a negative electrode active material selected from one or more of the following: lithium metal, a metal or metalloid that can be alloyed with lithium, and a carbonaceous material. Examples of the negative electrode active material may include a metal or metalloid, and a carbonaceous material. The metal or metalloid may include, for example, Li, In, Al, Sn, Si, or an alloy thereof. The carbonaceous material may include, for example, artificial graphite, graphite carbon fiber, resin sintered carbon, pyrolysis vapor growth carbon, coke, intermediate carbon microbeads (MCMB), furfuryl alcohol, polyphenylene, pitch-based carbon fiber, vapor growth carbon fiber, natural graphite, and non-graphitizable carbon. The negative electrode active material may be used alone or as a combination of at least two selected therefrom.
[0085] The solid electrolyte included in the negative electrode active material layer 22 may be a solid electrolyte of formula (1) according to an embodiment. Alternatively, the solid electrolyte included in the negative electrode active material layer 22 may be a mixture of a solid electrolyte of formula (1) and a solid electrolyte different from the solid electrolyte of formula (1) according to an embodiment. In order to prepare the negative electrode layer 20, additives such as a conductive agent, a binder, a filler, a dispersant, or an ion conductive agent may be appropriately mixed in addition to the negative electrode active material and the solid electrolyte. The additives added to the negative electrode layer 20 may be the same as those added to the above-mentioned positive electrode layer 10.
[0086] Solid electrolyte layer
[0087] The solid electrolyte layer 30 may include a solid electrolyte between the positive electrode layer 10 and the negative electrode layer 20. The solid electrolyte layer 30 may further include a binder. The solid electrolyte included in the solid electrolyte layer 30 may be the solid electrolyte of formula (1) according to an embodiment. Alternatively, the solid electrolyte included in the solid electrolyte layer 30 may be a mixture of the solid electrolyte of formula (1) and a second solid electrolyte different from the solid electrolyte of formula (1).
[0088] In an embodiment, the second solid electrolyte may be, for example, a sulfide solid electrolyte. The sulfide solid electrolyte may be, for example, aLi 2 S-(1-a)P 2 S 5 (where 0 < a < 1), aLi 2 S-bP 2 S 5 -cLiX (where X is a halogen atom, such as F, Cl, Br, I, or a combination thereof, where 0 < a < 1, 0 < b < 1, 0 < c < 1, and a + b + c = 1), aLi 2 S-bP 2 S 5 -cLi 2 O (where 0 < a < 1, 0 < b < 1, 0 < c < 1, and a + b + c = 1), aLi 2 S-bP 2 S 5 -cLi 2 O-dLiI (where 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 < d < 1, and a + b + c + d = 1), aLi 2 S-(1-a)SiS 2 (where 0 < a < 1), aLi2 S -bSiS 2 -cLiI (0 < a < 1, 0 < b < 1, 0 < c < 1, and a + b + c = 1), aLi 2 S-bSiS 2 -cLiBr (where 0 < a < 1, 0 < b < 1, 0 < c < 1, and a + b + c = 1), aLi 2 S-bSiS 2 -cLiCl (where 0 < a < 1, 0 < b < 1, 0 < c < 1, and a + b + c = 1), aLi 2 S-bSiS 2 -cB 2 S 3 -dLiI (where 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 < d < 1, and a + b + c + d = 1), aLi 2 S-bSiS 2 -cP2 S 5 -dLiI (where 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 < d < 1 and a + b + c + d = 1), aLi 2 S - (1 - a)B 2 S 3 (where 0 < a < 1), aLi 2 S - bP 2 S 5 -cZ m S n (where m and n are each independently a positive integer between 1 and 10, Z is Ge, Zn or Ga, and where 0 < a < 1, 0 < b < 1, 0 < c < 1, and a + b + c = 1), aLi 2 S - (1 - a)GeS 2 (where 0 < a < 1), aLi 2 S - bSiS 2 -cLi 3 PO 4 (where 0 < a < 1, 0 < b < 1, 0 < c < 1, and a + b + c = 1), and aLi 2 S - bSiS 2 -cLi P MO q (where p and q are each independently a positive integer between 1 and 10, where 0 < a < 1, 0 < b < 1, 0 < c < 1, and a + b + c = 1, and M can be P, Si, Ge, B, Al, Ga, In). Here, the sulfide solid electrolyte can be prepared by treating starting materials of the sulfide solid electrolyte (e.g., Li 2 S or P 2 S 5 ) according to the dissolution quenching method or mechanical grinding. Further, after such treatment, the obtained sulfide solid electrolyte can be sintered. When additional sintering is performed, the sulfide solid electrolyte can become more rigid.
[0089] The all - solid - state secondary battery 1 according to an embodiment can include the solid electrolyte according to the embodiment, and thus, can exhibit high characteristics in a wide temperature range.
[0090] Method for manufacturing an all - solid - state secondary battery
[0091] Next, a method for manufacturing the all - solid - state secondary battery 1 will be described. After preparing the positive electrode layer 10, the negative electrode layer 20, and the solid electrolyte layer 30 according to the method described below, and then stacking the prepared layers, the all - solid - state secondary battery 1 can be manufactured.
[0092] Solid electrolyte manufacturing process
[0093] The solid electrolyte according to the embodiment can be prepared according to the following preparation method. First, a mechanical milling process can be performed to mix Li 2 S.P. 2 S 5 , and LiBr are mixed to obtain a glassy composite. Here, the mechanical grinding process can be performed using a planetary ball mill at a rotation speed in the range of about 50 rpm to about 600 rpm together with 1 kg of 1-100 kWh / raw material mixture for 0.1-50 hours. In an embodiment, the mechanical grinding is performed at a temperature of about 25 ° C and in an inert atmosphere such as an argon atmosphere. Therefore, the solid electrolyte can be prepared more easily and reliably.
[0094] Then, the glassy composite thus obtained can be heat-treated at the glass transition temperature of the composite or more to convert the glassy composite into an ion-conducting glass ceramic. Such an ion-conducting glass ceramic corresponds to a solid electrolyte according to an embodiment. Then, the ion-conducting glass ceramic can be cooled to obtain a solid electrolyte. The solid electrolyte thus obtained can be crushed to a desired degree and then used to prepare an all-solid-state secondary battery 1. Here, the temperature when the heat treatment is performed is not particularly limited as long as the temperature is greater than the glass transition temperature of the glassy composite. The glass transition temperature of the glassy composite according to an embodiment may be about 200°C, and in this regard, the temperature at which the heat treatment can be performed is in the range of about 250°C to about 450°C, and, for example, about 350°C to about 450°C. As the heat treatment temperature increases, the ionic conductivity of the solid electrolyte tends to increase.
[0095] Method for preparing positive electrode layer
[0096] The positive electrode layer 10 may be prepared according to any suitable method, including known preparation methods. For example, the materials constituting the positive electrode active material layer 12 (e.g., positive electrode active material, solid electrolyte, binder, etc.) may be added to a non-polar solvent to prepare a slurry (also referred to as a slurry paste). The slurry thus obtained may be spread on the positive electrode collector 11 and then dried. The resulting stacked layer may be rolled (rolled) to prepare the positive electrode layer 10. In another embodiment, the mixture of materials constituting the positive electrode active material layer 1 may undergo consolidation (compaction, consolidation)-molded into a disc or may undergo stretching into a sheet to prepare the positive electrode layer 10. When the positive electrode layer 10 is prepared by these methods, the use of the positive electrode collector 11 may be omitted. Manufacturing process of the negative electrode layer
[0097] First, the material constituting the negative electrode active material layer 22 (e.g., negative electrode active material, solid electrolyte, binder, etc.) may be added to a non-polar solvent to prepare a slurry. Then, the slurry thus obtained may be spread on the negative electrode current collector 21 and then dried. The resulting stacked layer may be rolled under pressure to prepare the negative electrode layer 20. In another embodiment, the mixture of materials constituting the negative electrode active material layer 22 may undergo consolidation-molding into a disc or may undergo stretching into a sheet to prepare the negative electrode layer 20. When the negative electrode layer 20 is prepared by these methods, the use of the negative electrode current collector 21 may be omitted.
[0098] Solid electrolyte layer manufacturing process
[0099] The solid electrolyte can be formed by using a known film forming method such as a blasting method, an aerosol deposition method, a cold spray method, a sputtering method, a chemical vapor deposition (CVD) method, a spraying method, etc. to prepare a solid electrolyte layer 30. Moreover, the solid electrolyte layer 30 may further undergo a pressing solid electrolyte assembly. In another embodiment, the solid electrolyte layer 30 may also be prepared as follows: the solid electrolyte is mixed with a solvent, an adhesive, or a support (carrier), and the mixture is pressed. Here, the adhesive or support may be added for the purpose of enhancing the integrity of the solid electrolyte layer 30 or preventing a short circuit of the solid electrolyte layer 30.
[0100] Preparation of all-solid-state secondary batteries
[0101] The positive electrode layer 10 , the negative electrode layer 20 , and the solid electrolyte layer 30 prepared by the above method may be stacked to sandwich the solid electrolyte layer 30 therebetween and then rolled (roll-pressed) to prepare the all-solid secondary battery 1 according to the embodiment.
[0102] Example
[0103] Example 1
[0104] Preparation of solid electrolyte
[0105] First, measure the reagent Li 2 S.P. 2 S 5 , and LiBr to correspond to the desired composition (Li 5.75 PS 4.75 Br 1.25 ) structure, and subjected to mechanical grinding treatment to mix the raw materials in a planetary ball mill for 20 hours. The mechanical grinding treatment was carried out at room temperature (ca. 25° C.) and in an argon atmosphere at a rotation speed of 380 rpm.
[0106] 300 mg of Li5.75 PS 4.75 Br 1.25 A powder sample (ie, a glassy composite) of the composition (at about 400 MPa / cm2) 2 ) was pressed at a pressure of 1.0°C / min to obtain a disc having a diameter of about 13 millimeters (mm) and a thickness of about 0.8 mm. The disc thus obtained was coated with a gold film and further placed in a carbon furnace. Thus, a sample for heat treatment was prepared. The sample thus obtained was vacuum sealed by using a quartz glass tube. However, the temperature of the vacuum-sealed sample was increased from room temperature to a temperature of 450°C at a heating rate of 1.0°C / min using an electric furnace, heat treated at a temperature of 450°C for 6 hours, and then cooled to room temperature at a cooling rate of 1.0°C / min, thereby obtaining a block of a solid electrolyte. The collected block was crushed by using an agate mortar to obtain a sample of Example 1 (solid electrolyte). X-ray powder diffraction was performed on the solid electrolyte, and it was confirmed that the desired crystals having a argyrodite crystal structure were formed in the solid electrolyte. Figure 1 The results of X-ray diffraction analysis are shown. The X-ray diffraction analysis of Example 1 revealed peaks at the above positions of 25.16°±0.50°2θ, 29.65°±0.50°2θ, 30.94°±0.50°2θ, 44.36°±0.50°2θ, 47.22°±0.50°2θ, and 51.75°±0.50°2θ, which are consistent with the solid electrolyte of formula (1).
[0107] In addition, the baseline was removed from the X-ray diffraction data (ie, diffraction spectrum) measured by this method. Then, when the maximum intensity of the peak at 29.65°±0.5°2θ was referred to as IA and the maximum intensity of the peak at 28.0°±0.5°2θ was referred to as IB, IB / IA was measured to be 0.07.
[0108] Evaluation of solid electrolyte properties
[0109] The ionic conductivity of the solid electrolyte thus obtained was measured as follows. 2 The disc was pressed with a pressure of 100 μm to prepare a disc. Then, In foil (having a thickness of 500 μm) was provided on both surfaces of the disc to prepare a disc for measuring ionic conductivity. The ionic conductivity of the disc was measured at 27° C. by using an AC impedance measurement device. The disc for measuring ionic conductivity exhibited a conductivity of 1.8×10 -3Siemens / centimeter (S / cm) of ionic conductivity. In addition, the ionic conductivity was measured while changing the temperature to 27 ° C, 40 ° C, 50 ° C, 60 ° C, 70 ° C, and 80 ° C, and the activation energy was calculated from the results. As a result, the solid electrolyte has an activation energy of 26.4 kilojoules / mole (kJ / mol).
[0110] Example 2
[0111] A solid electrolyte was prepared in the same manner as in Example 1, except that the temperature at which the heat treatment was performed was changed to 350° C. X-ray diffraction measurement was performed on the solid electrolyte, and it was confirmed that the desired crystals having an argyrodite crystal structure were present in the solid electrolyte. The results of the X-ray analysis are shown in Figure 1 The X-ray diffraction analysis of Example 2 revealed a peak at the above position, which is consistent with the solid electrolyte of formula (1). In addition, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA was 0.08. In addition, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27° C. was 3.1×10 -3 S / cm. Therefore, as a result of calculating the activation energy in the same manner as in Example 1, the solid electrolyte had an activation energy of 25.2 kJ / mol.
[0112] Example 3
[0113] A solid electrolyte was prepared in the same manner as in Example 1, except that the desired composition was Li 5.50 PS 4.50 Br 1.50 The solid electrolyte was subjected to X-ray diffraction measurement, and it was confirmed that the desired crystals having the argyrodite crystal structure were present in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 1 The X-ray diffraction analysis of Example 3 revealed a peak at the above position, which is consistent with the solid electrolyte of formula (1). In addition, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA was 0.08. In addition, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27° C. was 5.5×10 - 3 S / cm. Furthermore, as a result of calculating activation energy in the same manner as in Example 1, the solid electrolyte had an activation energy of 28.4 kJ / mol.
[0114] Example 4
[0115] A solid electrolyte was prepared in the same manner as in Example 3, except that the temperature at which the heat treatment was performed was changed to 350° C. X-ray diffraction measurement was performed on the solid electrolyte, and it was confirmed that the desired crystals having an argyrodite crystal structure were present in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 1 The X-ray diffraction analysis of Example 4 revealed a peak at the above position, which is consistent with the solid electrolyte of formula (1). In addition, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA was 0.09. In addition, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27° C. was 3.6×10 -3 S / cm. Furthermore, as a result of calculating activation energy in the same manner as in Example 1, the solid electrolyte had an activation energy of 28.4 kJ / mol.
[0116] Example 5
[0117] A solid electrolyte was prepared in the same manner as in Example 3, except that the temperature at which the heat treatment was performed was changed to 250° C. X-ray diffraction measurement was performed on the solid electrolyte, and it was confirmed that the desired crystals having an argyrodite crystal structure were present in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 1 The X-ray diffraction analysis of Example 5 revealed a peak at the above position, which is consistent with the solid electrolyte of formula (1). In addition, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA was 0.43. In addition, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27° C. was 2.3×10 -3 S / cm. Furthermore, as a result of calculating activation energy in the same manner as in Example 1, the solid electrolyte had an activation energy of 28.8 kJ / mol.
[0118] Example 6
[0119] A solid electrolyte was prepared in the same manner as in Example 1, except that the desired composition was Li 5.77 PS 4.77 Br 1.23 The solid electrolyte was subjected to X-ray diffraction measurement, and it was confirmed that the desired crystals having the argyrodite crystal structure were present in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 1The X-ray diffraction analysis of Example 6 revealed a peak at the above position, which is consistent with the solid electrolyte of formula (1). In addition, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA was 0.07. In addition, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27° C. was 1.7×10 - 3 S / cm. Furthermore, as a result of calculating activation energy in the same manner as in Example 1, the solid electrolyte had an activation energy of 27.1 kJ / mol.
[0120] Example 7
[0121] A solid electrolyte was prepared in the same manner as in Example 6, except that the temperature at which the heat treatment was performed was changed to 350° C. X-ray diffraction measurement was performed on the solid electrolyte, and it was confirmed that the desired crystals having an argyrodite structure were present in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 1 The X-ray diffraction analysis of Example 7 revealed a peak at the above position, which is consistent with the solid electrolyte of formula (1). In addition, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA was 0.05. In addition, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27° C. was 1.6×10 -3 S / cm. Furthermore, as a result of calculating activation energy in the same manner as in Example 1, the solid electrolyte had an activation energy of 26.0 kJ / mol.
[0122] Comparative Example 1
[0123] A solid electrolyte was prepared in the same manner as in Example 1, except that the composition of the solid electrolyte was Li 6.00 PS 5.00 Br 1.00 and the temperature at which the heat treatment is performed is changed to 550° C. X-ray diffraction measurement is performed on the solid electrolyte, and it is confirmed that crystals having an argyrodite crystal structure exist in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 3In. X-ray diffraction analysis of Comparative Example 1 revealed peaks similar to those of Example 1 at the above positions, but the solid electrolyte composition of Comparative Example 1 did not satisfy 1.2 < x < 1.75 in formula (1). In addition, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA was 0.04. In addition, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27 °C was 5.7×10 -4 S / cm. In addition, as a result of calculating the activation energy in the same manner as in Example 1, the solid electrolyte had an activation energy of 35.4 kJ / mol.
[0124] Comparative Example 2
[0125] A solid electrolyte was prepared in the same manner as in Comparative Example 1, except that: the temperature during the heat treatment was changed to 450 °C. X-ray diffraction measurement was performed on the solid electrolyte, and it was confirmed that crystals having a thiogermanate crystal structure were present in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 3 In. X-ray diffraction analysis of Comparative Example 2 revealed peaks similar to those of Example 1 at the above positions, but the solid electrolyte composition of Comparative Example 2 did not satisfy 1.2 < x < 1.75 in formula (1). In addition, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA was 0.03. In addition, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27 °C was 1.7×10 -3 S / cm. In addition, as a result of calculating the activation energy in the same manner as in Example 1, the solid electrolyte had an activation energy of 31.2 kJ / mol.
[0126] Comparative Example 3
[0127] A solid electrolyte was prepared in the same manner as in Comparative Example 1, except that: the temperature during the heat treatment was changed to 350 °C. X-ray diffraction measurement was performed on the solid electrolyte, and it was confirmed that crystals having a thiogermanate crystal structure were present in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 3 In. The X-ray diffraction spectrum of Comparative Example 3 had peaks similar to those of Example 1 at the above positions, but the solid electrolyte composition of Comparative Example 3 did not satisfy 1.2 < x < 1.75 in formula (1). In addition, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA was 0.02. In addition, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27 °C was 1.0×10-3 S / cm. In addition, as a result of calculating the activation energy in the same manner as in Example 1, the solid electrolyte has an activation energy of 31.1 kJ / mol.
[0128] Comparative Example 4
[0129] A solid electrolyte was prepared in the same manner as in Example 1, except that: the desired composition was Li 6.25 PS 5.25 Br 0.75 and the temperature at which the heat treatment was to be carried out was changed to 350 °C. X-ray diffraction measurement was performed on the solid electrolyte, and it was confirmed that crystals having an argyrodite crystal structure were present in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 3 . The X-ray diffraction spectrum of Comparative Example 4 has peaks similar to those of Example 1 at the above positions, but the solid electrolyte composition of Comparative Example 4 does not satisfy 1.2 < x < 1.75 in formula (1). In addition, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA was 0.00. In addition, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27 °C was 1.9×10 -3 S / cm. In addition, as a result of calculating the activation energy in the same manner as in Example 1, the solid electrolyte has an activation energy of 31.7 kJ / mol.
[0130] Comparative Example 5
[0131] A solid electrolyte was prepared in the same manner as in Comparative Example 1, except that: the temperature at which the heat treatment was to be carried out was changed to 250 °C. X-ray diffraction measurement was performed on the solid electrolyte, and it was confirmed that crystals having an argyrodite crystal structure were present in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 3 . The X-ray diffraction spectrum of Comparative Example 5 has peaks similar to those of Example 1 at the above positions, but the solid electrolyte composition of Comparative Example 5 does not satisfy 1.2 < x < 1.75 in formula (1). In addition, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA was 0.00. In addition, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27 °C was 1.8×10 -3 S / cm. In addition, as a result of calculating the activation energy in the same manner as in Example 1, the solid electrolyte has an activation energy of 30.8 kJ / mol.
[0132] Comparative Example 6
[0133] A solid electrolyte was prepared in the same manner as in Example 1, except that: the desired composition was Li 6.50 PS 5.50 Br 0.50 and the temperature at which the heat treatment was carried out was changed to 550 °C. X-ray diffraction measurement was performed on the solid electrolyte, and it was confirmed that crystals having a thiogermanate crystal structure were present in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 3 . The X-ray diffraction analysis of Comparative Example 6 had peaks similar to those of Example 1 at the above positions, but the solid electrolyte composition of Comparative Example 6 did not satisfy 1.2 < x < 1.75 in formula (1). In addition, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA was 0.00. Further, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27 °C was 1.3×10 -3 S / cm. In addition, as a result of calculating the activation energy in the same manner as in Example 1, the solid electrolyte had an activation energy of 39.5 kJ / mol.
[0134] Comparative Example 7
[0135] A solid electrolyte was prepared in the same manner as in Comparative Example 6, except that: the temperature at which the heat treatment was carried out was changed to 450 °C. X-ray diffraction measurement was performed on the solid electrolyte, and it was confirmed that crystals having a thiogermanate crystal structure were present in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 3 . The X-ray diffraction analysis of Comparative Example 7 had peaks similar to those of Example 1 at the above positions, but the solid electrolyte composition of Comparative Example 7 did not satisfy 1.2 < x < 1.75 in formula (1). In addition, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA was 0.00. Further, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27 °C was 1.2×10 -3 S / cm. In addition, as a result of calculating the activation energy in the same manner as in Example 1, the solid electrolyte had an activation energy of 39.8 kJ / mol.
[0136] Comparative Example 8
[0137] A solid electrolyte was prepared in the same manner as in Example 1, except that: the desired composition was Li 6.75 PS 5.75 Br 0.25and the temperature during the heat treatment is changed to 550 °C. X-ray diffraction measurement is performed on the solid electrolyte, and it is confirmed that crystals having an argyrodite crystal structure are present in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 3 . The X-ray diffraction analysis of Comparative Example 8 has peaks similar to those of Example 1 at the above positions, but the solid electrolyte composition of Comparative Example 8 does not satisfy 1.2 < x < 1.75 in formula (1). Further, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA is 0.00. Further, the ionic conductivity of the solid electrolyte is measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27 °C is 6.8×10 -4 S / cm. Further, as a result of calculating the activation energy in the same manner as in Example 1, the solid electrolyte has an activation energy of 44.7 kJ / mol.
[0138] Comparative Example 9
[0139] A solid electrolyte is prepared in the same manner as in Comparative Example 8, except that: the temperature during the heat treatment is changed to 450 °C. X-ray diffraction measurement is performed on the solid electrolyte, and it is confirmed that crystals having an argyrodite crystal structure are present in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 3 . The X-ray diffraction analysis of Comparative Example 9 has peaks similar to those of Example 1 at the above positions, but the solid electrolyte composition of Comparative Example 9 does not satisfy 1.2 < x < 1.75 in formula (1). Further, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA is 0.00. Further, the ionic conductivity of the solid electrolyte is measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27 °C is 7.9×10 -4 S / cm. Further, as a result of calculating the activation energy in the same manner as in Example 1, the solid electrolyte has an activation energy of 41.1 kJ / mol.
[0140] Comparative Example 10
[0141] A solid electrolyte is prepared in the same manner as in Example 1, except that: the desired composition is Li 5.25 PS 4.25 Br 1.75 . X-ray diffraction measurement is performed on the solid electrolyte, and it is confirmed that crystals having an argyrodite crystal structure are present in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 3In the X-ray diffraction analysis of Comparative Example 10, there were peaks similar to those of Example 1 at the above positions, but the solid electrolyte composition of Comparative Example 10 did not satisfy 1.2 < x < 1.75 in Formula (1). Further, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA was 0.29. Further, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27 °C was 7.9×10 -4 S / cm. Further, as a result of calculating the activation energy in the same manner as in Example 1, the solid electrolyte had an activation energy of 41.1 kJ / mol.
[0142] Comparative Example 11
[0143] A solid electrolyte was prepared in the same manner as in Comparative Example 10, except that: the temperature during the heat treatment was changed to 350 °C. X-ray diffraction measurement was performed on the solid electrolyte, and it was confirmed that there were crystals having a thiogermanate crystal structure in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 3 In the X-ray diffraction analysis of Comparative Example 11, there were peaks similar to those of Example 1 at the above positions, but the solid electrolyte composition of Comparative Example 11 did not satisfy 1.2 < x < 1.75 in Formula (1). Further, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA was 0.66. Further, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27 °C was 7.1×10 -4 S / cm. Further, as a result of calculating the activation energy in the same manner as in Example 1, the solid electrolyte had an activation energy of 44.6 kJ / mol.
[0144] Comparative Example 12
[0145] A solid electrolyte was prepared in the same manner as in Comparative Example 10, except that: the temperature during the heat treatment was changed to 250 °C. X-ray diffraction measurement was performed on the solid electrolyte, and it was confirmed that there were crystals having a thiogermanate crystal structure in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 3In the X-ray diffraction analysis of Comparative Example 12, there are peaks similar to those of Example 1 at the above positions, but the solid electrolyte composition of Comparative Example 12 does not satisfy 1.2 < x < 1.75 in Formula (1). In addition, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA is 2.81. Further, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27 °C was 5.2×10 -4 S / cm. In addition, as a result of calculating the activation energy in the same manner as in Example 1, the solid electrolyte has an activation energy of 50.1 kJ / mol.
[0146] Comparative Example 13
[0147] A solid electrolyte was prepared in the same manner as in Example 1, except that: reagent Li 2 S, P 2 S 5 and LiCl were measured to form a desired composition of the formula Li 5.75 PS 4.75 Cl 1.25 and the temperature at which the heat treatment was to be carried out was changed to 550 °C. X-ray diffraction measurement was performed on the solid electrolyte, and it was confirmed that there were crystals having a thiogermanate crystal structure in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 3 In the X-ray diffraction analysis of Comparative Example 13, there are peaks similar to those of Example 1 at the above positions, but the solid electrolyte composition of Comparative Example 13 is not the composition represented by Formula (1). In addition, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA is 0.00. Further, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27 °C was 2.3×10 -3 S / cm. In addition, as a result of calculating the activation energy in the same manner as in Example 1, the solid electrolyte has an activation energy of 37.0 kJ / mol.
[0148] Comparative Example 14
[0149] A solid electrolyte was prepared in the same manner as in Example 1, except that: reagent Li 2 S, P 2 S 5 Na 2 S, and LiCl were measured to form the formula (Li 5.69 Na 0.06 )PS 4.75 Cl 1.25The desired composition and the temperature at which the heat treatment is to be carried out are changed to 550 °C. X-ray diffraction measurement is performed on the solid electrolyte, and it is confirmed that crystals having an argyrodite crystal structure are present in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 3 . The X-ray diffraction analysis of Comparative Example 14 has peaks similar to those of Example 1 at the above positions, but the solid electrolyte composition of Comparative Example 14 is not the composition represented by formula (1). Further, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA is 0.00. Further, the ionic conductivity of the solid electrolyte is measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27 °C is 5.1×10 -3 S / cm. Further, as a result of calculating the activation energy in the same manner as in Example 1, the solid electrolyte has an activation energy of 34.0 kJ / mol.
[0150] Comparative Example 15
[0151] A solid electrolyte is prepared in the same manner as in Example 1, except that: the desired composition is Li 5.80 PS 4.80 Br 1.20 and the temperature at which the heat treatment is to be carried out is changed to 450 °C. X-ray diffraction measurement is performed on the solid electrolyte, and it is confirmed that crystals having an argyrodite crystal structure are present in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 3 . The X-ray diffraction analysis of Comparative Example 15 has peaks similar to those of Example 1 at the above positions, but the solid electrolyte composition of Comparative Example 15 does not satisfy 1.2 < x < 1.75 in formula (1). Further, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA is 0.4. Further, the ionic conductivity of the solid electrolyte is measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27 °C is 1.7×10 -3 S / cm. Further, as a result of calculating the activation energy in the same manner as in Example 1, the solid electrolyte has an activation energy of 30.0 kJ / mol.
[0152] Comparative Example 16
[0153] A solid electrolyte is prepared in the same manner as in Comparative Example 15, except that: the temperature at which the heat treatment is to be carried out is changed to 350 °C. X-ray diffraction measurement is performed on the solid electrolyte, and it is confirmed that crystals having an argyrodite crystal structure are present in the solid electrolyte. The results of the X-ray diffraction analysis are shown in Figure 3In the X-ray diffraction analysis of Comparative Example 16, there were peaks similar to those of Example 1 at the above positions, but the solid electrolyte composition of Comparative Example 16 did not satisfy 1.2 < x < 1.75 in Formula (1). Further, as a result of measuring IB / IA in the same manner as in Example 1, IB / IA was 0.05. Further, the ionic conductivity of the solid electrolyte was measured in the same manner as in Example 1, and the ionic conductivity of the solid electrolyte at 27 °C was 1.3x10 -3 S / cm. Further, as a result of calculating the activation energy in the same manner as in Example 1, the solid electrolyte had an activation energy of 30.2 kJ / mol.
[0154] The properties of Examples 1-7 and Comparative Examples 1-16 are provided in Tables 1-4 and are arranged according to the heat treatment temperature.
[0155] Table 1
[0156]
[0157] Table 2
[0158]
[0159] Table 3
[0160]
[0161] Table 4
[0162]
[0163] Evaluation
[0164] When comparing Examples 1-7 with Comparative Examples 1-16, the solid electrolytes prepared according to Examples 1-7 satisfied the requirements of Formula (1) and had a high solid electrolyte ionic conductivity (1.6×10 -3 S / cm or greater) and a low activation energy (less than 30 kJ / mol). At the same time, the solid electrolytes prepared according to Comparative Examples 1-16 did not satisfy the requirements of the solid electrolyte according to Formula (1). More specifically, the solid electrolytes prepared according to Comparative Examples 1-17 had a high ionic conductivity but also had an increased activation energy (about 30 kJ / mol or greater). Therefore, it is expected that all the solid electrolytes prepared according to Examples 1-7 exhibit excellent characteristics in a wide temperature range.
[0165] It should be understood that the embodiments described herein should be considered only in the descriptive sense and not for limiting purposes. The description of features or aspects within each embodiment should typically be considered applicable to other similar features or aspects in other embodiments.
[0166] Although one or more embodiments have been described with reference to the drawings, it will be understood by those of ordinary skill in the art that various changes in form and details may be made therein without departing from the spirit and scope as defined by the following claims.
Claims
1. A solid electrolyte for an all-solid-state secondary battery, wherein the solid electrolyte has a composition represented by the formula (1): Li 7-x P.S. 6-x Br x (1), where 1.23 ≤ x ≤ 1.5, the solid electrolyte has a thioargentite crystal structure, and when analyzed by X-ray diffraction using CuKα radiation, the solid electrolyte has at least one peak at a position of 29.65° ± 0.50° 2θ, where the solid electrolyte further satisfies (IB / IA) < 0.5, where when analyzed by X-ray diffraction using CuKα radiation, IA is the maximum intensity of the peak at the position of 29.65° ± 0.50° 2θ, and IB is the maximum intensity of the peak at the position of 28.00° ± 0.50° 2θ.
2. The solid electrolyte according to claim 1, wherein IB / IA is less than 0.
1.
3. The solid electrolyte according to claim 1, wherein when analyzed by X-ray diffraction using CuKα radiation, the solid electrolyte has peaks at positions of 25.16° ± 0.50° 2θ, 29.65° ± 0.50° 2θ, 30.94° ± 0.50° 2θ, 44.36° ± 0.50° 2θ, 47.22° ± 0.50° 2θ, and 51.75° ± 0.50° 2θ.
4. The solid electrolyte according to claim 1, wherein the solid electrolyte has an activation energy of 29 kJ / mol or less.
5. The solid electrolyte according to claim 1, wherein the solid electrolyte has a thermal conductivity of 1.6 x 10 -3 Ionic conductivity of Siemens / cm or greater.
6. A composite electrode, which comprises an electrode active material and a first solid electrolyte, and the first solid electrolyte is the solid electrolyte according to any one of claims 1-5.
7. The composite electrode according to claim 6, wherein the electrode active material is a positive electrode active material or a negative electrode active material.
8. The composite electrode according to claim 6, which further comprises a second solid electrolyte, wherein the second solid electrolyte is different from the first solid electrolyte.
9. The composite electrode according to claim 6, which further comprises a sulfide solid electrolyte.
10. An all-solid-state secondary battery, which comprises: a positive electrode layer; a negative electrode layer; and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer and comprising a first solid electrolyte, and the first solid electrolyte is the solid electrolyte according to any one of claims 1-5.
11. The all-solid-state secondary battery according to claim 10, wherein the positive electrode layer comprises a positive electrode active material, and the positive electrode active material comprises a lithium-containing ternary transition metal oxide having a layered rock salt structure.
12. The all-solid-state secondary battery according to claim 11, wherein the lithium ternary transition metal oxide is composed of LiNi x Co y Al z O2 or LiNi x Co y Mn z O2 said, where 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1.
13. The all-solid-state secondary battery according to claim 10, wherein the negative electrode layer comprises a negative electrode active material, and the negative electrode active material comprises at least one of the following: lithium metal, a metal or a metalloid capable of alloying with lithium, or a carbonaceous material.
14. An all-solid-state secondary battery as described in claim 13, wherein the negative electrode active material comprises lithium, indium, aluminum, tin, silicon, artificial graphite, graphite carbon fiber, resin sintered carbon, pyrolysis vapor-grown carbon, coke, intermediate carbon microbeads, furfuryl alcohol, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, non-graphitizable carbon, or a combination thereof. 15 . The all-solid-state secondary battery according to claim 10 , wherein the solid electrolyte layer further comprises a second solid electrolyte different from the first solid electrolyte. 16 . The all-solid-state secondary battery according to claim 10 , wherein the solid electrolyte layer further comprises a sulfide solid electrolyte.
17. A method for preparing a solid electrolyte, the method comprising: Mechanically grinding a mixture including Li2S, P2S5, and LiBr in a mixing ratio corresponding to formula (1) to obtain a glassy composite; and heat-treating the glassy composite at a glass transition temperature of the glassy composite or more to convert the glassy composite into an ion-conductive glass-ceramic and obtain a solid electrolyte, The solid electrolyte has the formula (1): composition: Li 7-x P.S. 6-x Br x (1), Where 1.23≤x≤1.5, wherein the solid electrolyte further satisfies (IB / IA)<0.5, Wherein IA is the maximum intensity of a peak at a position of 29.65°±0.50° 2θ, and IB is the maximum intensity of a peak at a position of 28.00°±0.50° 2θ when analyzed by X-ray diffraction using CuKα radiation.
18. The method of claim 17, wherein the mechanical grinding is performed at a temperature of 25°C and in an inert atmosphere.
19. The method of claim 17, wherein the mechanical grinding is performed using a planetary ball mill.
20. The method of claim 19, wherein the mechanical grinding using a planetary ball mill is performed at a rotation speed of 50-600 rpm for 0.1-50 hours.
21. The method of claim 17, wherein the temperature when the heat treatment of the glassy composite is performed is in the range of 250°C to 450°C.
22. The method of claim 17, further comprising cooling the ion conductive glass ceramic after the heat treatment of the glassy composite to obtain a solid electrolyte.
23. The method of claim 17, wherein the solid electrolyte has an argyrodite crystal structure.
